PENGARUH AKUNTABILITAS,TRANSPARANSI DAN PARTISIPASI TERHADAP ALOKASI DANA DESA DALAM MEWUJUDKAN GOOD GOVERNANCE (STUDI KASUS PADA DESA DI KECAMATAN PAPAR KEDIRI) - Widuri, Sani; Tohari, Amin; Zaman, Badrus (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to analyze the effect of accountability, transparency and participation on the allocation of village funds in realizing Good Governance in villages in the Papar District, Kediri Regency. Data collection was carried out by giving questionnaires to village officials who met the criteria in the Papar District, Kediri Regency. The research respondents were 80 respondents who had a background in the process of managing Village Fund Allocations, this study used a quantitative approach with associative panelman technique which was used to reveal problems that were causal in nature between two variables or more. Diana's research model using multiple linear regression with SPSS version 23 program. The results of this study are that accountability, transparency and partial participation have a significant effect on the allocation of village funds in realizing Good Governance in Villages in Papar District.